Program Analisis Frekuensi Besaran Rancangan Berbasis Website - Dwi Prasetyo, Ginanjar; Achmad, Nizar; Widyasari, Titiek (Institut Teknologi Bandung, 2024)
Abstract The design of hydraulic structures involves extensive calculations, one of that is frequency analysis. The advancement of technology should be leveraged to facilitate these calculations. A website serves as an efficient application of technology for frequency analysis, especially when compared to manual calculations. The data used for this analysis consists of daily rainfall data from 11 stations in Sleman Regency from 2004 to 2018. The data analysis was conducted by comparing calculations using Microsoft Excel and the PHP: Hypertext Preprocessor programming language. This research resulted in a web-based frequency analysis tool capable of performing calculations for distribution selection, Chi-Square test, Smirnov-Kolmogorov test, and design magnitude for specific return periods (2, 5, 10, 20, 25, 50, and 100 years). The program demonstrates a high degree of accuracy, with an average relative error of 0.049. However, there is a significant relative error in the Log Pearson III distribution, particularly in the Smirnov-Kolmogorov test, where the relative error reaches 4.155. Another limitation of this website is the input format, which requires numerical data with a period (.) as a decimal separator to avoid calculation errors. This website can be generally used with rainfall or discharge data from the study area being planned. Keywords : Frequency analysis, design magnitude, rain distribution, PHP: hypertext preprocessor, website